08.07 Blood chemokine profile in untreated early rheumatoid arthritis: cxcl10 as a disease activity marker. (1st March 2017) - Pandya, Jayesh M; Lundell, Anna-Carin; Andersson, Kerstin; Nordström, Inger; Theander, Elke; Rudin, Anna
Abstract : Background/purpose: Pathogenic mechanisms in early and preclinical stages of rheumatoid arthritis are unclear. We have recently analysed the profile of T cell subtypes based on chemokine receptor expression in blood from untreated early rheumatoid arthritis (ueRA) patients compared to healthy controls (HC). Here, we compared the levels of the respective chemokines in blood plasma of ueRA patients with those of HC. We also studied the association of chemokine levels with the proportions of circulating T cell subsets and the clinical disease activity. Methods: Peripheral blood was obtained from 43 patients with ueRA satisfying the ACR 2010 criteria and who had not received any DMARD or prednisolone, and from 14 sex- and age-matched HC. Proportions of T helper cells in blood, including Th0, Th1, Th2, Th17, Th1Th17, TFh, and regulatory T cells were defined by flow cytometry. Fifteen chemokines, including several CXCL and CCL chemokines related to the T cell subtypes as well as to other major immune cells were measured in blood plasma using flow cytometry bead-based immunoassay or ELISA. Clinical disease activity in patients was evaluated by assessing the following parameters: DAS28, Clinical Disease Activity Index (CDAI), Swollen Joint Counts (SJC), Tender Joint Counts (TJC), CRP and ESR. The data was analysed using multivariate factor analyses followed by univariate analyses. Results: Multivariate discriminant analysis showed that patients with ueRA separate from HC based on the blood plasma chemokine profile. The best discriminators were CXCL9, CXCL10, CXCL13, CCL4 and CCL22, which were significantly higher in ueRA compared to HC in univariate analyses. Among the chemokines analysed, only CXCL10 correlated with multiple disease activity measures, including DAS28-CRP, DAS28-ESR, CDAI, SJC in 66 joints, CRP and ESR. Conclusions: High circulating levels of CXCL10 in plasma of ueRA and the association with the clinical disease activity suggests that CXCL10 may serve as a disease activity marker in early RA.